The international handbook of FRP composites in civil engineering - Zoghi, Manoochehr, 1956- (Taylor & Francis/CRC Press, 2013)
"Applications of high-performance fiber reinforced polymer (FRP) composite materials have grown beyond just aerospace and marine industries, into civil engineering and other related disciplines. This book provides a complete primer on FRP composites, including history, constituent materials, and basic mechanics and properties. It focuses on professional applications, such as nondestructive testing and evaluation, composites for reinforcement, design philosophies, and guidelines. It also includes helpful formulas, tables, and charts for easy reference and standards of practice from the UK, Scandinavia, Japan, the US, China, Australia, and other countries"--